2016
DOI: 10.3389/fphar.2016.00129
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist Targeting microRNA-155 Protects against Lithium-Pilocarpine-Induced Status Epilepticus in C57BL/6 Mice by Activating Brain-Derived Neurotrophic Factor

Abstract: Epilepsy is a severe brain disorder affecting numerous patients. Recently, it is inferred that modulation of microRNA-155 (miR-155) could serve as a promising treatment of mesial temporal lobe epilepsy. In the current study, the therapeutic potential of miR-155 antagonist against temporal lobe epilepsy (TLE) was evaluated and the underlying mechanism involved in this regulation was explored. TLE model was induced by lithium-pilocarpine method. The effect of miR-155 antagonist on epilepticus symptoms of TLE mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…A recent study showed that delivery of antagomirs targeting microRNA-155 prior to status epilepticus induced by pilocarpine in mice resulted in a trend toward lower mortality and lower scores in a Racine-type behavioral assessment and suggested brain-derived neurotrophic factor as a possible target. The effects of the antagomir on post-status epilepticus epilepsy or neuropathology were not reported (36).…”
Section: Micrornas With Potential Seizure-promoting (Proconvulsive) Ementioning
confidence: 99%
“…A recent study showed that delivery of antagomirs targeting microRNA-155 prior to status epilepticus induced by pilocarpine in mice resulted in a trend toward lower mortality and lower scores in a Racine-type behavioral assessment and suggested brain-derived neurotrophic factor as a possible target. The effects of the antagomir on post-status epilepticus epilepsy or neuropathology were not reported (36).…”
Section: Micrornas With Potential Seizure-promoting (Proconvulsive) Ementioning
confidence: 99%
“…Meanwhile, the brain tissue samples of the neocortex with TLE could only be obtained from drug-resistant epileptic patients. For this reason, a pilocarpine-induced epileptic mouse model that has been broadly used as a model for human TLE has obvious advantages in repeating the results of the epileptic patients284546. Thus, we performed our study on brain tissues of both TLE patients and experimental mice using two complementary methods to further investigate the expression of NR4A1 and the potential mechanism of TLE.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted the pilocarpine‐induced SE model of mice, which is a well‐established chemical‐induced model for TLE. Although the use of lithium is not universal, recent studies used lithium, combined with scopolamine, to reduce the overall pilocarpine dose in a mice TLE model . Pilocarpine is a muscarinic acetylcholine receptor agonist acting on M1 subunit of G protein–coupled receptors that damages the hippocampus, resulting in the generation of SE .…”
Section: Discussionmentioning
confidence: 99%